Posterior Tibial Nerve Schwannoma Mimicking Tarsal Tunnel Syndrome (Global Journal of Medical Research, 2019)
Schwannomas are benign, encapsulated tumors derived from myelin sheath of nerves. They usually occur in the head and neck region and are uncommon in the extremities. The authors present a case of a schwannoma of the posterior tibial nerve sheath resulting in tarsal tunnel syndrome of the foot. The diagnosis, in this case, is made within two weeks of presentation and surgery is scheduled. The mass was excised measuring 1.1×0.9 cm and sent to pathology which confirmed the diagnosis of schwannoma of the posterior tibial nerve. The recommended therapeutic modality remains to be the complete excision of the tumor.
Keywords: schwannoma; tarsal tunnel